Nurses’ perception of postural defects among children and adolescents - Kurc, Katarzyna; Krajewska-Kułak, Elżbieta; Lewko, Lewko (Nursing in the 21st Century, 2013)
NURSES’ PERCEPTION OF POSTURAL DEFECTS AMONG CHILDREN AND ADOLESCENTS Introduction. The occurrence of postural defects at the developmental age is estimated at approximately 50-60% of the population according to the region. Aim. To assess nurses’ knowledge about the most common postural defects among children and adolescents, the style of life of children and young people and prevention posture in children and adolescents. Materials and methods. The present study included 100 randomly selected second-year nursing students. We used the original questionnaire. Results. Most respondents (89%) reported that faulty postures were more frequent. Nurses gave correct answers about round back – 42%, the back concave – 39%, knee valgus – 32%, knee varus – 34%, pectus excavatum – 62%, chicken chest – 73% flat feet – 83%. According to the respondents the correct posture is influenced by exercise and proper nutrition (93%), footwear (86%), mattress (67%), physical activity in the fresh air (56%), swimming (67%). According to 67% of nurses, knowledge during studies was appropriate about posture in children and adolescents, and 89% of them would like to expand their knowledge in this field. According to 64% of the respondents due to a high prevalence of postural defects, physiotherapists should be employed in the school. Conclusions. The level of professional knowledge of nursing students of the Faculty of Health Sciences, Medical University of Bialystok on the most common postural defects in children and adolescents, lifestyle, and prevention of the postural defects in children and adolescents is good. The best source of knowledge about the postural defects was obtained in the course of education in university. According to most the surveyed nurses, physical therapist should be employed in the school.